Quantitative profiling of protein-DNA binding on microarrays. - Ragoussis, J; Field, S; Udalova, I (2006)
Recent studies on genome-wide localization of transcription factor (TF) binding to DNA have shown that a large proportion of identified sequences do not contain consensus motifs predicted by databases of transcription factor binding sites, such as TRANSFAC. The main limitation of these databases is that they are based on a literature search of published examples of binding; consequently the data are not from a systematic survey and may be subject to sampling biases if investigators focused on particular motifs. Thus, there is an urgent need for systematic profiling of vertebrate transcription factor binding to DNA. We have developed a high-throughput platform for the quantitative analysis of protein-DNA interactions based on microarray technology.